(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Postmenopausal women experience a lot of health problems, often which musculoskeletal issues being very common. The drop in estrogen levels after menopause can bring on some problems like weaker muscles, bone loss, and weight gain affecting mental and physical health that leads to restrictions in daily life activities. Objective: The objective of this study was to find out the prevalence of musculoskeletal complains among postmenopausal women in twin cities. Methodology: This cross-sectional study was conducted in Rawalpindi and Islamabad, including housewives and OPD patients. A total of 370 postmenopausal women participated. Data on pain patterns were collected using the Nordic questionnaire. Data was analyzed using SPSS version26. Result: Most participants were aged 50-60 years. The most common pain areas over the past year were the lower back (54.3%), knees (52.7%), and upper back (34.9%). In the past 7 days, knee (48.0%) and lower back pain (47.0%) were most frequent. Lower back pain limited daily activities the most (50%), followed by knee pain (44.6%). Many women sought treatment for these pains, particularly for the lower back and knees (36%). Conclusion: Musculoskeletal pain, particularly in the lower back and knees, is far and wide among postmenopausal ladies. It influences day to day existence and leads numerous to look for clinical assistance. Further research is needed to improve treatment options.